Overexpression of a Brassica rapa MADS-box gene, BrAGL20, induces early flowering time phenotypes in Brassica napus - Hong, Joon Ki; Kim, Soo-Yun; Kim, Kwang-Soo; Kwon, Soo-Jin; Kim, Jung Sun; Kim, Jin A.; Lee, Soo In; Lee, Yeon-Hee (Plant biotechnology reports, 2013)
BrAGL20 ( SOC1 ) containing MADS box, a floral integrator gene, was introduced into Brassica napus cv. “Youngsan” by Agrobacterium -mediated transformation. Constitutively overexpressed BrAGL20 under the CaMV 35S promoter induced early flowering time compared to the wild-type. These phenotypes were stably inherited through generations T 2 and T 3 , regardless of planting season. The expression of the floral meristem identity genes LFY and AP1 seemed to appear rapidly in the shoot apex region of transgenic plants showing the early flowering time phenotype. These results suggest that overexpression of BrAGL20 can significantly affect the flowering time of B. napus , and regulation of floral integrator gene expression could be applied for adaptation of crops to local environments and climate changes.